Orchids in El mundo vegetal de los Andes peruanos: A review and taxonomic update - Trujillo, Delsy (2022)
In the present work, the contribution to the knowledge of the orchids of Peru that Augusto Weberbauer made in his work El mundo vegetal de los Andes peruanos is analyzed. During his botanical studies, Weberbauer collected about 264 specimens of orchids, which not only served to enrich his work; but also served for other botanists to describe new species of orchids. Also, a list of the specimens of Weberbauer deposited in different herbariums is presented; grouped into four lists: 1) type material with specimens in herbarium collections, 2) type material without existing specimens in herbarium collections, 3) non-type material in herbarium collections, and 4) non-type material cited in the literature; and lectotypes are designated for 70 Orchidaceae names.